Heart rate variability and plasma norepinephrine concentration in diabetic dogs at rest - Pirintr,P. (Springer Netherlands, 2015)
Cardiac autonomic neuropathy in dogs with diabetic mellitus (DM) was evaluated using measurement of heart rate variability (HRV) and plasma norepinephrine (NE) concentration. Dogs were divided into 2 groups; the control non-DM group (n013) and the diabetic group (n022) which was further divided into the well-controlled DM (n011) and the poorly-controlled DM subgroups (n011) according to their fasting plasma fructosamine concentrations. The electrocardiogram (ECG) was recorded continuously for at least 30 min to yield HRV. The results showed that in the poorlycontrolled DM subgroup, the average of normal R-R interval (mean N-N), SD of the mean of all 5-min segments of normal RR intervals (SDANN) were lower than the control group while heart rate was higher (P<0.05). The NNA, SDNN, SDNN index and pNN50% were significantly lower when compared with the well-controlled DM subgroup (P<0.05). The high frequency (HF) and total power were significantly lower while the ratio of low to high frequency (LF/HF) was higher (P<0.05) when compared with the well-controlledDM subgroup. Moreover, in the poorly-controlled DM subgroup, plasma NE concentration was lower than the control group (210±37 vs. 479±74 pg/ml, P<0.05). There was a significantly negative correlation between plasma NE and plasma fructosamine concentrations. It is concluded that cardiac autonomic neuropathy occurred in poorly-controlled DM dogs. The sympathetic activity was suppressed as shown by decrease in both plasma NE concentration and LF component. © Springer Science+Business Media, LLC 2012.